Kajian Ekranisasi Novel dan Film Balada Sepasang Kekasih Gila - Alip Sujana; Dian Hartati (Jurnal Bahasa dan Sastra, 2022)
This study aims to describe the ecranization process that occurs in the characters, stories, and settings in the novel Balada Sepasang Kekasih Gila by Han Gagas with the film Balada Sepasang Kekasih Gila directed by Anggy Umbara. The data for this research are the novel Balada Sepasang Kekasih Gila by Han Gagas and the film Balada Sepasang Kekasih Gila, directed by Anggy Umbara. The research method used in this research is comparative descriptive. The source of the data in this research is the novel Balada Sepasang Kekasih Gila by Han Gagas with the film Balada Sepasang Kekasih Gila, directed by Anggy Umbara. Data collection techniques using libraries and observations. The results in this study indicate that: (1) The process of ecranization that occurs in the characters has reduced the number of characters from 7 characters to 3 characters. (2) The ecranization process in which stories are added, subtracted, and changed. (3) The process of ecranization that occurs in the setting of the place and time of the addition, subtraction, and changes. Based on the data that has been analyzed, it can be concluded that the process of curating the novel into the film form has various reductions, additions, and changes in the plot, characters, and storyline. This is done to adjust the duration shown in the film.